2022
DOI: 10.1186/s12874-022-01519-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of moderator by confounder interactions in the assessment of treatment effect modification: a simulation study

Abstract: Background When performed in an observational setting, treatment effect modification analyses should account for all confounding, where possible. Often, such studies only consider confounding between the exposure and outcome. However, there is scope for misspecification of the confounding adjustment when estimating moderation as the effects of the confounders may themselves be influenced by the moderator. The aim of this study was to investigate bias in estimates of treatment effect modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Our simulation study showed that the two “across subsets” and “within subsets” strategies achieve similar results in terms of bias and variance, provided that interaction terms between the subset variable and other covariates influencing the choice of treatment are incorporated. Otherwise, the omission of these interaction terms based on the “across subsets” strategy induced an important bias, regardless of the PS-based method used, which confirms previous results [ 33 , 34 ]. This bias led to the identification of an interaction that was not found with the other two strategies in our illustrative example.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our simulation study showed that the two “across subsets” and “within subsets” strategies achieve similar results in terms of bias and variance, provided that interaction terms between the subset variable and other covariates influencing the choice of treatment are incorporated. Otherwise, the omission of these interaction terms based on the “across subsets” strategy induced an important bias, regardless of the PS-based method used, which confirms previous results [ 33 , 34 ]. This bias led to the identification of an interaction that was not found with the other two strategies in our illustrative example.…”
Section: Discussionsupporting
confidence: 87%
“…The “within subsets” strategy was also slightly more robust than the “across subsets” strategy in this case. Although previous studies on this topic focused on PS matching without replacement [ 14 16 , 33 37 ], compared to the other methods, this method achieved a bias in the estimation of the treatment effect in our setting of large differences between subsets. This bias has been previously named the “unmatched patient bias” [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model specification, we assume the absence of interactions between covariates bold-italicX and Z for illustrative purposes. If such interactions exist, it is best to control for these additional interaction terms in the final outcome model as well as to assess the balance of the interaction between X and Z . 67 We also assume only 1 moderator of interest; if interest lies in the estimation of multiple M-ATEs, it is possible to repeat this procedure independently for each candidate moderator. In such a case, care should be taken to adjust for multiple hypothesis testing when estimating the additional models.…”
Section: Methodsmentioning
confidence: 99%
“…Propensity score methods and traditional regression modelling, such as G-computation, tend to yield similar results [11], but this has yet to be investigated within our field of interest. Simulation studies have revealed that the variable selection has a bearing on the result when using propensity scores [12][13][14][15], but for unemployment and health this have not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%